Innovative Teaching and Learning Approaches Integrating Interactive Sensor Technology and Emotional Intelligence in Early Childhood Education at TASKA - AQLIMAR NABILAH ZULKIFLI; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
This study examines innovative teaching and learning approaches integrating interactive sensor technology and emotional intelligence within early childhood education at TASKA. The research is driven by the growing need for holistic development in young children encompassing cognitive, emotional, and social domains. A qualitative case study design was employed to observe how teachers utilize interactive sensor-based tools such as touch panels, motion sensors, and emotion recognition systems to enhance children’s engagement and emotional regulation. Data collection involved classroom observations and teacher interviews. Findings reveal that combining digital interactivity with emotional learning strategies improves children’s self-awareness, cooperation, and motivation. This study underscores the importance of leveraging technology thoughtfully to foster socio-emotional growth and provides insights for educators striving to balance innovation with human connection in early childhood education